Teaching Method Used By Lecturer In Teaching English For Nursing Academy Program (A Study Of ESP) - Rangga Kusuma Admaja; Sulistyaningsih (JournEEL, 2020)
The background of this study is English Special Purpose, English Special Purpose has a specific term for each field. English has many functions in education or profession. English has many different purpose especially in Nurse Academy Program. Regarding to this case the teacher of English should be able to teach English for the students in Nursing Academy program with the appropriete teaching method. Based on the background of the study, the purpose of the study focuses to discribe the teaching method used by lecturer in nursing academy program and the responses’ students in English in their field. The Techniques of collecting data in this research are observation, interview and questionnaire. This is a qualitative research design the writer describe the data briefly. The result of observation and interview showed that Spiral Teaching Method was the teaching method used by the lecture in teaching English of Nursing Academy Program, the method was appropriete with the concept of English special purpose. Whereas, the results of the questionnaire explain about the resposes of the students showed that the student’s majority had a positive responses, it were showed that diagram were not presentage lower in 50% and the presentage was on 50% up to 100 % in each item question. The conclusion in this research is the lecturer implements method used to teach English for special purpose in nursing academy program very well and the students gave respond positively in English in their field.